(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
An eject power system with multi-gas generators was presented for the interior ballistic problem in variable-depth underwater launch. The computation mode of underwater interior ballistics was built. The simulation method was described for multi-depths launch. The interior ballistic simulation for missile launching at three different depths was carried out. The results show that at depth from 20 m to 60 m,the range of missile detached-velocity can be 18.9 m/s±3.4 m/s by successively firing the gas generators at certain intervals. The eject power system with multi-gas generators is an efficient way for the variable-depth underwater launch.